Omphalocele - Revivo Rinda Pratama; Roza Sri Yanti (Andalas Obstetrics And Gynecology Journal, 2022)
Objective: Reporting a case of omphalocele.Method: Case report.Result:Acaseofa32years-oldwoman, diagnosedwithG2P1A0H134-35weeksofpretermpregnancy+ previous Cesaran Section + omphalocele + fetal distress. According to ultrasonography, biometric measurements of the fetus were: BPD: 8.5 cm, FL: 6.4 cm, HL: 5.2 cm, AC: 27.8 cm, AFI: 23.3 cm, there were no image of abdominal wall, but a membrane surrounding the abdomen was visible. From the USG examination, the conclusion was Omphalocele.ChromosomalanalysiswasdoneusingG-Comparativetechnic,withresult46,XY,which means the amount of the chromosomes was 46, and sex chromosomes were XY. There was no major structural defect. Mostly, the disorders causing these conditions are 13, 18 and 21 trisomy, and Beckwith-WiedemannSyndrome.Conclusion: Omphalocele is a genetic disorder marked by failure of the abdominal organs to return into the abdominal cavity. It requires thorough and accurate prenatal examinations to establish a diagnosis. Keywords: Omphalocele, prenatal diagnosis